Analysis Of Mathematics Learning Media Based on Realistic Mathematics Learning Approaches to Improve Mathematical Problem-Solving Ability - Puspa, Indah; Prasetia, Indra (Holistic Science, 2023)
This study aims to analyze the results of mathematics learning media based on a mathematics learning approach and to improve the ability to solve mathematical problems. This type of research is qualitative research using the literature study method, so the data obtained from this research is secondary data derived from collections of literature such as journals that are relevant to the formulation of the research problem. Data analysis techniques by way of content analysis and explanatory analysis, namely, analyzing, describing and concluding the findings of the literature taken. The results of this study indicate that, (1) the results of the analysis of realistic mathematics learning media have practical, valid and effective qualities for improving mathematical problem solving abilities, (2) students' mathematical problem solving abilities after being analyzed by effective learning media.